Integrated approach to the formation of information and digital competence in future primary school teachers - Olga G. Yaroshenko; Olena D. Samborska (CTE Workshop Proceedings)
This article presents an expanded analysis of the experimental verification of an integrated approach to modernizing information and digital training of future primary school teachers. The research responds to the growing importance of digital competence in contemporary educational environments, particularly in light of the digital transformation of society. The study employed a comprehensive experimental design involving control and experimental groups of students at pedagogical colleges over a two-year period. The integrated approach encompassed all major forms of the educational process, including an author's elective course ``Modern Information and Digital Technologies in the Educational Process of Primary School''. Robust methodological support was developed, consisting of electronic teaching materials, interactive learning activities, and practical tasks embedded throughout the curriculum. Statistical analysis of cognitive, operational, and value components of students' information and digital (ID) competence confirmed the significant effectiveness of the integrated approach. The experimental group demonstrated markedly higher levels of digital competence formation across all measured dimensions. Beyond statistical validation, the research revealed how this approach better prepared future teachers for the challenges of online education during the COVID-19 pandemic. This study contributes to the theoretical understanding of digital competence formation in teacher education and provides practical insights for modernizing primary teacher preparation in the digital age.